2017
DOI: 10.1073/pnas.1620289114
|View full text |Cite
|
Sign up to set email alerts
|

Sensorimotor-independent development of hands and tools selectivity in the visual cortex

Abstract: The visual occipito-temporal cortex is composed of several distinct regions specialized in the identification of different object kinds such as tools and bodies. Its organization appears to reflect not only the visual characteristics of the inputs but also the behavior that can be achieved with them. For example, there are spatially overlapping responses for viewing hands and tools, which is likely due to their common role in object-directed actions. How dependent is occipitotemporal cortex organization on obj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
38
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 69 publications
(43 citation statements)
references
References 75 publications
5
38
0
Order By: Relevance
“…No participant had a history of psychiatric or neurological disorder. All the IDs had developed fine motor skills of the feet and used their feet for many typical hand-related actions of daily life (e.g., opening or closing doors; for more information about IDs' foot use see Vannuscorps et al 2014;Striem-Amit et al 2017) and none had history of phantom limb sensations or movements (tested as in Vannuscorps and Caramazza 2016). Two TDs were excluded from the sample due to poor behavioral performance (error rate exceeding the group mean by > 2 SDs) in the experimental task.…”
Section: Participantsmentioning
confidence: 99%
See 1 more Smart Citation
“…No participant had a history of psychiatric or neurological disorder. All the IDs had developed fine motor skills of the feet and used their feet for many typical hand-related actions of daily life (e.g., opening or closing doors; for more information about IDs' foot use see Vannuscorps et al 2014;Striem-Amit et al 2017) and none had history of phantom limb sensations or movements (tested as in Vannuscorps and Caramazza 2016). Two TDs were excluded from the sample due to poor behavioral performance (error rate exceeding the group mean by > 2 SDs) in the experimental task.…”
Section: Participantsmentioning
confidence: 99%
“…In favor of a critical role for experience, it has been shown that the emergence of the brain's typical area of specialization for letters requires reading experience (Baker et al 2007;Dehaene et al 2010;Saygin et al 2016). By contrast, the neural representation of tools and hands appears to be virtually the same in congenitally blind individuals Kitada et al 2014;Striem-Amit and Amedi 2014), individuals born without hands (Striem-Amit et al 2017), and in the typically developed population (Bracci et al 2012). Here, we investigated the role of sensorimotor experience in shaping the organization of the action observation network as a window on this question.…”
Section: Introductionmentioning
confidence: 99%
“…The purpose of this article is to offer further support for a cerebellum-driven social learning explanation of the evolution of stone-tool making. This additional support is based on the findings of the existence of (1) an innate hand-tool overlap in the cerebrum [ 55 ] and (2) specific tool modules in the lateral posterior cerebellum for both actual and imagined tool use [ 56 , 57 ].…”
Section: Introduction and Evolutionary Pastmentioning
confidence: 99%
“…The cerebellum’s dentate nucleus sends both actual tool use and imaginary tool use models to the cerebral cortex where they can be consciously experienced [ 58 ] . Second , in studying dysplasics (individuals born without hands), Striem-Amit, Vannuscope, and Caramazza [ 55 ] have described the evolution of an innate hand-tool overlap area in the occipital–temporal area of the cerebral cortex for the acceptance of tools into the hand: The hand tool overlap would have emerged because of the potential advantage that accrues from the efficient processing of hands and tools as parts of a common (or closely intertwined), specialized system [tools being advantageous ancillaries. This system, in turn, is connected to the dorsal, action-processing areas [parietal cortex] to allow quick and efficient shaping of hands to grasp and use tools [requiring both phylogenetic and ontogenetic cerebellar refinement].…”
Section: Introduction and Evolutionary Pastmentioning
confidence: 99%
“…Since such task-directed organization in the visual cortex is found in people born blind, it cannot be based on visual experience alone. Furthermore, it is likely not based on one's sensory or motor experience alone, as visual handselectivity patterns are also found in people born without hands [12]. Support for this model has also been provided from the auditory cortex, showing task-specificity from other senses in deafness [13,14].…”
mentioning
confidence: 95%